Early Childhood Motor Development and Body Mass Index: A Demography Study of Children Aged 4-5 Years in Rural Area - Putri, Wulandari; Stephani, Mesa Rahmi; Sumarno, Gano (Universitas Pendidikan Indonesia, 2020)
A child motor development and body mass index are determinant aspects yet important predictors for other aspect of development. However, both of them are also influenced by other factors, including the parents’ socioeconomic status. Therefore, this study was aimed at finding out the relationship between parents’ socioeconomic status with the children’ motor development and body mass index, especially for the children living in rural area. The study was an ex-post facto study. The study used Ages and Stages Questionnaire (ASQ) 3rd Edition to measure the children motor development and Instrument (Scale) for Measuring the Socioeconomic Status of a Family Questionnaire to measure the socioeconomic status of the parents. The children body mass index were calculated from the height and weight. The study involved 64 children as the participants. However, only 53 data of the children that were eligible to be analyzed after the data cleaning process was conducted. The data were analyzed by using statistic calculation by the help of SPSS application. The results of the study found that most of the children were coming from upper middle and lower middle status. Their body mass index were mostly in thin category. However, their motor development seems to be on the schedule. Only a small number of the children who need more activities or further professional assessment. Moreover, there was no significant relationship between the parents’ socioeconomic status and the children motor development and body mass index was found. The study indicates that the children weight status were alarming and need further attention. However, the data were taken from a small number of participant, thus it cannot be generalized to summarize a general depiction of all children in rural area.